Pengaruh Permainan Uno Stacko Untuk Kemampuan Mengenal Lambang Bilangan 1-10 Pada Anak - Gita Nisa Aulia (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2024)
The activities carried out to stimulate the ability to recognize the symbols of numbers 1-10 are using the uno stacko game. This study aims to determine the effect of the uno stacko game on the ability to recognize symbols of numbers 1-10 in children. . This research uses quantitative research using Pre-Experimental, namely the One Group Pretest Posttest Design type. The sample of this study was group A children aged 4-5 years with 31 children as samples.. The hypothesis test in this study used the Paired Sample Test which is part of the parametric statistical analysis because it meets the requirements that the data is normally distributed. Based on the results of the Paired Sample Test test criteria, the result is that the sig. 2 - tailed, namely 0.000 <0.05, it can be said that Ho is rejected and Ha is accepted, so it can be interpreted that there is an influence of the uno stacko game on the ability to recognize number symbols 1-10. Based on the results of the calculation of the N-Gain Score test, the percentage results were 65%, so it can be concluded that the effect of the uno stcko game on the ability to recognize number symbols 1-10 in children is 67% which is included in the medium category.